- #1

The Head

- 144

- 2

- Homework Statement
- If dy/dy + y = (1-1/x)(1/(2y)), solve when x=1, y=1/sqrt(2). Hint: Use a substitution to get into the form of a first order differential equation

- Relevant Equations
- integrating factor = e^integral(P(x))

v=y^(1-n)

dy/dx +P(x)y=Q(x)y^n

I seem to be getting an unsolvable integral here (integral calculator says it's an Ei function, which I've never seen). My thought was to use Bernoulli to make it linear and then integrating factors. Is that wrong? The basic idea is below:

P(x) 1, Q(x) = 1/2(1-1/x), n=-1, so use v=y^1- -1)=y^2

so y=sqrt(v), dy/dx=1/(2sqrt(v))dv/dx

Thus the equation becomes 1/(2sqrt(v))dv/dx + sqrt(v) = 1/sqrt(v) * 1/2(1-1/x))

Multiplying by 2* sqrt(v) gives dv/dx +2 v = (1-1/x)

Use the integrating factor e^2x gives: d/dx(v*e^(2x)) =e^(2x)(1-1/x) = e^(2x) - e^(2x)*1/x

ve^(2x) then just equals the antiderivative of e^(2x) - e^(2x)*1/x, but that second term seems to give a problem. Is my method incorrect? Not sure how to proceed.

P(x) 1, Q(x) = 1/2(1-1/x), n=-1, so use v=y^1- -1)=y^2

so y=sqrt(v), dy/dx=1/(2sqrt(v))dv/dx

Thus the equation becomes 1/(2sqrt(v))dv/dx + sqrt(v) = 1/sqrt(v) * 1/2(1-1/x))

Multiplying by 2* sqrt(v) gives dv/dx +2 v = (1-1/x)

Use the integrating factor e^2x gives: d/dx(v*e^(2x)) =e^(2x)(1-1/x) = e^(2x) - e^(2x)*1/x

ve^(2x) then just equals the antiderivative of e^(2x) - e^(2x)*1/x, but that second term seems to give a problem. Is my method incorrect? Not sure how to proceed.